2022
DOI: 10.1155/2022/5798941
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on Therapeutic Effect and Mechanism of Propolis on Wound Healing

Abstract: Propolis is a kind of reduct collected by bees from various plant sources. Because propolis is a mixture, it has a variety of biological activities, excellent anti-inflammatory and bactericidal effects. Especially in the treatment of infectious wounds, acute wounds, burns, and scalds and promoting wound healing, more and more scientists began to apply it to the research field of wound healing. The standard preparation of propolis combined with other compound components has a safer and less toxic effect in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 104 publications
0
18
0
4
Order By: Relevance
“…Wound healing is a recovering process of damaged tissues by replacing dysfunctional injured cellular structures. 1 occurred through three main phases; inflammation, proliferative, and tissue remodeling 2 to form a complex and continuous process but dynamic and orderly process, characterized by a series of overlapping of these interact phases. Honey is one of the oldest known medicines which have been "rediscovered" in later times by the medical profession, especially for dressing wounds management since its effectiveness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wound healing is a recovering process of damaged tissues by replacing dysfunctional injured cellular structures. 1 occurred through three main phases; inflammation, proliferative, and tissue remodeling 2 to form a complex and continuous process but dynamic and orderly process, characterized by a series of overlapping of these interact phases. Honey is one of the oldest known medicines which have been "rediscovered" in later times by the medical profession, especially for dressing wounds management since its effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…23 It was found that propolis can decrease scar formation, shorten healing time, boost wound contraction, accelerate tissue repair, and ultimately improve patients' quality of life in skin wound healing. 2 Otherwise, the release of honeypropolis-engineered collagen peptides in the wound site increases the absorption and re-epithelization of keratinocytes. 10 Reducing bacterial biofilm production: Biofilm production is a passive virulence factor facilitating many infectious diseases 79 where certain bacterial genes produce extracellular polysaccharides to protect these pathogens from antimicrobial agents and cellular immune elements 80 resulting in long standing chronic wounds.…”
Section: Introductionmentioning
confidence: 99%
“…Propolis is believed to have antibacterial, anti-inflammatory, antiseptic, antimycotic, anesthetic, spasmolytic, antifungal, antiulcer, anticancer, and immunomodulatory properties [ 13 , 15 ], as well as wound-healing properties. It can decrease scar formation, shorten healing time, boost wound contraction, accelerate tissue repair, and ultimately improve patients’ quality of life in skin wound healing [ 16 ]. More than 300 different compounds were characterized so far, including aliphatic acid, fatty acids, ketones, terpenoids, vitamins, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Propolis has been used by humans therapeutically to treat inflammation and infectious diseases [ 3 , 4 , 5 , 6 , 7 , 8 ]. Numerous studies have revealed a range of biological activities of propolis, including antibacterial, antifungal, antiviral, anticancer, anti-inflammatory, immunomodulatory, and antioxidant activities [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Although the anti-inflammatory and immunomodulatory activities of propolis are well established (reviewed in [ 16 , 17 ]), it is still unclear how propolis components could contribute to all of these biological properties.…”
Section: Introductionmentioning
confidence: 99%